Diagnosis and Etiology of Seedling Mortality in Cavendish Banana (Musa acuminata L.) at PT Great Giant Pineapple Nursery - Nugraha, Rafi Dwi; Lestari, Safira Rizka (Journal of Applied Plant Technology, 2025)
This study aimed to diagnose the causes of seedling mortality in Cavendish banana (Musa acuminata L.) at PT Great Giant Pineapple Nursery. Clinical symptoms observed included leaf wilting, root rot, and blackened corms, primarily under high-humidity conditions. Laboratory isolation and morphological identification confirmed four fungal pathogens as the primary etiological agents: Heart rot (Phytophthora sp.), Aspergillus rot (Aspergillus sp.), fruit rot (Rhizopus sp.), and damping-off (Pythium sp.). Phytophthora sp. was particularly aggressive, causing severe vascular necrosis. Environmental factors such as excessive moisture, poor drainage, and contaminated nursery substrates were found to exacerbate disease incidence. The findings underscore the need for improved nursery management, including strict sanitation, optimized irrigation, and preventive fungicide applications. Recommendations also include the use of disease-free planting materials and enhanced ventilation to reduce fungal proliferation. Implementing these measures can significantly decrease seedling mortality and improve the production of healthy Cavendish banana plants.